Spontaneous and radiation-induced renal tumors in the Eker rat model of dominantly inherited cancer. - Hino, O (1993)
Hereditary renal carcinoma (RC) in the rat, originally reported by R. Eker in 1954, is an example of a Mendelian dominant predisposition to a specific cancer in an experimental animal. At the histologic level, RCs develop through multiple stages from early preneoplastic lesions (e.g., atypical tubules) to adenomas in virtually all heterozygotes by the age of 1 year. The homozygous mutant condition is lethal at approximately 10 days of fetal life. Ionizing radiation induces additional tumors in a linear dose-response relationship, suggesting that in heterozygotes two events (one inherited, one somatic) are necessary to produce tumors, and that the predisposing gene is a tumor suppressor gene. No genetic linkage has yet been found between the Eker mutation and rat DNA sequences homologous to those in human chromosome 3p, the presumed site of the putative tumor suppressor gene responsible for human RC. Nonrandom loss of rat chromosome 5 in RC-derived cell lines is sometimes associated with homozygous deletion of the interferon gene loci at rat chromosome bands 5q31-q33. Since this locus is not linked with the predisposing inherited gene in the Eker rat, it probably represents a second tumor suppressor gene involved in tumor progression.